FAKTOR-FAKTOR PENENTU STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - fitriyanto, nur (Universitas Muhammadiyah Tangerang, 2020)
Management policy in determining capital structure is one example of a vital policy in managing a company. Many companies expect to have an optimal capital structure to maximize the profits of shareholders. The purpose of this study is to examine the influence of several determinants of capital structure, such as business risk, growth opportunities, non-debt tax shields, sharia compliance, profitability and tangibility to corporate leverage moderated by company size. The population of this study were companies that have entered the IDX30 index criteria, with a purposive sampling method obtained by a sample of 14 companies. Test equipment used in this study uses panel data regression and Moderated Regression Analysis (MRA). The findings of this study in model I are profitability and non-debt tax shields have a significant negative effect on corporate leverage, firm size has a significant positive effect on company leverage, business risk has a significantly positive effect on firm leverage. Meanwhile, sharia compliance, growth opportunities and tangibility are not significant. The findings of model II found that only the variable non-debt tax shields and tangibility are able to be moderated by company size.